2022
DOI: 10.1186/s12944-022-01672-4
|View full text |Cite
|
Sign up to set email alerts
|

Peri-event plasma PCSK9 and hsCRP after an acute myocardial infarction correlate with early deterioration of left ventricular ejection fraction: a cohort study

Abstract: Background It is important to identify patients at increased risk of worsening of left ventricular ejection fraction (LVEF) after a myocardial infarction (MI). We aimed to identify the association of various potential biomarkers with LVEF impairment after an MI in South American patients. Methods We studied adult patients admitted to a University Hospital and diagnosed with an acute MI. Plasma concentrations of high-sensitivity C-reactive protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Likewise, a recent observational study identified a correlation between circulating PCSK9 levels and left ventricular ejection fraction (LVEF) after MI [ 12 , 13 ]. Furthermore, another observational study, which included a significant proportion of patients with IHD, established a link between PCSK9 and the prognosis of HF [ 14 ]. Taken together, our proteome-wide MR results and these previous findings indicate the involvement of PCSK9 in the development of ischemic HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a recent observational study identified a correlation between circulating PCSK9 levels and left ventricular ejection fraction (LVEF) after MI [ 12 , 13 ]. Furthermore, another observational study, which included a significant proportion of patients with IHD, established a link between PCSK9 and the prognosis of HF [ 14 ]. Taken together, our proteome-wide MR results and these previous findings indicate the involvement of PCSK9 in the development of ischemic HF.…”
Section: Discussionmentioning
confidence: 99%
“…In the BIOSTAT-CHF cohort, it was observed that circulating PCSK9 levels were notably elevated in HF patients, correlating positive correlation with the risk of mortality in this population [ 12 ]. Additionally, other observational studies have independently established a link between circulating PCSK9 levels and a diminished left ventricular ejection fraction (LVEF) following myocardial infarction (MI) [ 13 , 14 ]. These findings suggest the potential of PCSK9 as a viable therapeutic target for HF.…”
Section: Introductionmentioning
confidence: 99%
“…In the FOURIER study, the reduction of absolute occurrence risk of the endpoint events after using evolocumab in stable atherosclerotic patients with previous myocardial infarction was three times as much as in patients without previous myocardial infarction (137,138). Similarly, in the ODYSSEY OUTCOMES study, the use of alirocumab in addition to statin treatment significantly reduced the risk of MACEs and death in patients with ACS, which is more significant in patients with previous myocardial infarction (139). The level of plasma PCSK9 is positively correlated with hs-CRP in myocardial infarction patients (140).…”
Section: Pcsk9 and Myocardial Infarctionmentioning
confidence: 94%